2018
DOI: 10.1101/370577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radiosensitivity is an acquired vulnerability of PARPi-resistant BRCA1-deficient tumors

Abstract: The homologous recombination (HR) defect in BRCA1-associated cancers can be therapeutically exploited by the treatment with DNA-damaging agents and poly (ADPribose) polymerase (PARP) inhibitors. We and others previously reported that BRCA1deficient tumors are initially hypersensitive to the inhibition of topoisomerase I/II and PARP, but acquire drug resistance through restoration of HR activity by the loss of endresection antagonists of the 53BP1/RIF1/REV7/Shieldin/CST pathway. Here, we identified radiotherapy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The K14 cell line was generated by removing breast tumors from K14-Cre Brca1 f/f Trp53 f/f females, seeding single-cell suspensions in DMEM (Corning) supplemented with 10% FBS, and passaging until phenotypical and growth rate stability were achieved (22). The murine isogenic cell line pair KB1P-G3 −/+ BRCA1 was generated and maintained as previously described (12,13). All cell lines were routinely tested for the presence of Mycoplasma using the MycoAlert Mycoplasma Detection Kit (Lonza).…”
Section: Cell Culturementioning
confidence: 99%
“…The K14 cell line was generated by removing breast tumors from K14-Cre Brca1 f/f Trp53 f/f females, seeding single-cell suspensions in DMEM (Corning) supplemented with 10% FBS, and passaging until phenotypical and growth rate stability were achieved (22). The murine isogenic cell line pair KB1P-G3 −/+ BRCA1 was generated and maintained as previously described (12,13). All cell lines were routinely tested for the presence of Mycoplasma using the MycoAlert Mycoplasma Detection Kit (Lonza).…”
Section: Cell Culturementioning
confidence: 99%
“…A recent study on radiotherapy resistance mechanisms in Brca1-deficient mouse mammary tumors showed that this resistance is not caused by Tp53bp1 mutations. This observation directed experiments showing that PARPi-resistant tumors with BRCA1 and TP53BP1 mutations are still sensitive to radiotherapy [65,100]. This vulnerability opens opportunities to treat HR-restored PARPi-resistant tumors with irradiation, and further research should focus on validating this effect in other conditions of HR reactivation, notably following loss of factors such as Shieldin and DYNLL1.…”
Section: Acquired Vulnerabilities Of Parpi-resistant Tumorsmentioning
confidence: 99%
“…Counteracting PARPi‐resistant cancers currently represents a major clinical challenge. In addition to pyridostatin, the G4 ligand CX‐5461 (Zimmer et al , 2016; Xu et al , 2017), the alkylating agent chlorambucil (Tacconi et al , 2019), ionising radiation (Dev et al , 2018; Barazas et al , 2019) and cisplatin (Bunting et al , 2012; Cruz et al , 2018; Dev et al , 2018) have been reported as DNA damaging treatments that can counteract PARPi resistance in BRCA1/2‐deficient cells and tumours. However, only one clinical trial has so far investigated the cisplatin sensitivity in PARPi‐resistant BRCA1‐deficient tumours (Ang et al , 2013).…”
Section: Discussionmentioning
confidence: 99%